Timely regulated sorting from early to late endosomes is required to maintain cerebellar long-term depression - Taegon Kim (Nature Portfolio, 2017)
Long term depression (LTD) of the cerebellum is known to be mediated by postsynaptic trafficking of glutamate receptor AMPAR. Here, Kim and colleagues show that early- to late-endosomal sorting of AMPAR represents the switch from expression to maintenance phase of cerebellar LTD.